Glucose Intolerance on Phaeochromocytoma and Paraganglioma—The Current Understanding and Clinical Perspectives - Abe, Ichiro; Islam, Farhadul; Lam, Alfred King-Yin (Frontiers in Endocrinology, 2020)
Half of the patients with phaeochromocytoma had glucose intolerance which could be life-threatening as well as causing postoperative hypoglycaemia. Glucose intolerance is due to impaired insulin secretion and/or increased insulin resistance. Impaired insulin secretion is caused by stimulating adrenergic α2 receptors of pancreatic β-cells and increased insulin resistance is caused by stimulating adrenergic α1 and β3 receptors in adipocytes, α1 and β2 receptors of pancreatic α-cells and skeletal muscle. Furthermore, different affinities to respective adrenergic receptors exist between epinephrine and norepinephrine. Clinical studies revealed patients with phaeochromocytoma had impaired insulin secretion as well as increased insulin resistance. Furthermore, excess of epinephrine could affect glucose intolerance mainly by impaired insulin secretion and excess of norepinephrine could affect glucose intolerance mainly by increased insulin resistance. Glucose intolerance on paraganglioma could be caused by increased insulin resistance mainly considering paraganglioma produces more norepinephrine than epinephrine. To conclude, the difference of actions between excess of epinephrine and norepinephrine could lead to improve understanding and management of glucose intolerance on phaeochromocytoma.